N-terminal acetylation of transcription factor LIP induces immune therapy resistance via suppression of PD-L1 expression in non-small cell lung cancer - Xing Gao; Xiang He; Yongshuo Liu; Feiyu Tang; Yuxi Tian; Siyuan Gong; Jia Shen; Aimin Wang; Lunquan Sun; Wensheng Wei; Liang Weng (Journal for ImmunoTherapy of Cancer)
Background Programmed death-1 (PD-1) checkpoint blockade has revolutionized cancer therapy, yet its clinical success is confined to a subset of patients, underscoring the urgent need to understand the molecular underpinnings of programmed cell death ligand 1 (PD-L1) expression to combat immunotherapy resistance.Methods Employing CRISPR/Cas9 screening, we identified key regulators of PD-L1 in non-small cell lung cancer (NSCLC) cells, focusing on the transcription factor CEBPB and its isoform liver-enriched inhibitory protein (LIP). Through chromatin immunoprecipitation (ChIP) and luciferase reporter assays, we explored the interaction between LIP and basic-helix-loop-helix E22 (BHLHE22) in controlling PD-L1 transcription. We also used immunofluorescence and NBD-CI assays to examine how N-terminal acetylation affects LIP’s subcellular localization. The impact of LIP on tumor growth was assessed via subcutaneous tumorigenicity assays, while immunohistochemistry and immunofluorescence were used to analyze LIP-induced alterations in the tumor immune microenvironment.Results Our research indicates that CEBPB, particularly its LIP isoform, significantly suppresses PD-L1 expression in NSCLC cells. This suppression is contingent on LIP’s N-terminal acetylation by the N-terminal acetyltransferase A complex, which facilitates LIP’s nuclear entry and interaction with BHLHE22. This interaction leads to the formation of a co-repressor complex at the PD-L1 promoter, effectively reducing PD-L1 expression and enhancing the tumor immune response.Conclusions Identifying CEBPB, especially the LIP isoform, as a pivotal regulator of PD-L1 expression sheds light on the mechanisms behind PD-1 blockade resistance in NSCLC. Our findings suggest that modulating LIP’s function or its molecular interactions might offer a novel approach to boosting the efficacy of immunotherapies.